Magnetocaloric properties and specifics of the hysteresis at the first-order metamagnetic transition in Ni-doped FeRh - Chirkova, A. M.; Skokov, K. P.; Skourski, Yurii; Scheibel, Franziska; Karpenkov, A. Y.; Volegov, A. S.; Baranov, Nikolai V; Nielsch, Kornelius; Schultz, L.; Mueller, K-H; Woodcock, T. G.; Gutfleisch, Oliver (Physical Review Materials, 2021)
Measurements of the magnetization in quasistatic and pulsed magnetic fields with different sweep rates, measurements of the specific heat in various magnetic fields, and direct measurements of the adiabatic temperature change have been employed to study the metamagnetic phase transition from an antiferromagnetic (AF) to the ferromagnetic (FM) state in an (Fe0.98Ni0.02)49Rh51 alloy with a critical AF-FM transition temperature, Ttr, reduced to 266 K. Based on the obtained results, a magnetic phase diagram for this alloy has been constructed. The AF-FM transition induced by the magnetic field below 10 K is found to occur in a steplike fashion in contrast to smooth behavior at 10K<T<Ttr. The adiabatic temperature change ΔTad in the magnetic field of 2 T exceeds 6.5 K in pulsed fields (∼100 T/s) and in the Halbach setup (∼0.5 T/s), which is in agreement with the estimation from the S-T diagram constructed based on the specific heat measurements. The reversible ΔTad reaches -4.6 K under cyclic conditions in the Halbach setup (2 T). A complete transformation to the FM state in the whole temperature range requires a magnetic field of 14 T. Direct measurements of ΔTad in pulsed fields of 14 T revealed an irreversible part of the magnetocaloric effect associated with the presence of magnetic hysteresis and respective losses during the magnetization process.
CRIS-Team Scopus Importer:2022-04-14